Unfaithful - Lyne, Adrian (2002)
A thriller you cannot resist. from the director of Fatal attraction comes " a steamy thriller" (People Magazine) about sexual passion so intense, it consumes everything... and everyone... in its path Richard Gere is outstanding and Diane Lane's " slow-burning, fiercely erotic performance charges the movie". (Rolling Stone) Edward and Connie Summer (Gere, Lane) have the perfect life: a happy marriage, an eight-year-old son, a beautiful house in the suburbs... But when Connie's chance encounter with a seductive stranger (Oliver Martinez) erupts into full- blown affair, passion becomes obsession, and the true price of betrayal takes shattering toll. Charged with heart-pounding suspense and erotic thrills, Unfaithful is "sensational"